Study of Correlation Between Benthic Macroinvertebrates Distribution and Substrate Composition in Recreational Rivers - Abas, Athirah (2016)
This study was carried out as a method of biological monitoring for water quality by finding the correlation between benthic macroinvertebrates and substrate composition in recreational river. The objective was to propose a more simple yet reliable method in order to monitor the river’s health other than carrying out a common physical or chemical method. The study was carried out in the recreational rivers in Kelantan namely Bukit Bakar, Jeram Pasu and Lata Mengaji. Each sampling site was divided into five stations. Benthos was sampled by using surber net at three different points in each station. The substrate composition was determined by carrying out pebble count method where the intermediate axes of minimum 100 pebbles were measured and recorded. Two replications of sampling were done for the sampling. Benthos which had been collected was identified up to family level by using microscope. The substrate collected was categorized base on their size categories and analyze. The median (D50) of all substrates in each sampling site was determined in order to correlate with the total numbers of families identified. The correlation between benthic macroinvertebrates and substrate composition was determined by using Pearson Correlation. The results showed that Bukit Bakar possessed the highest correlation value. The other two sampling sites had low correlation values due to the substrate composition that were not balanced. Other than finding the correlation, this study also showed that a normal distribution of substrate composition was very important in order to find the correlation with the benthos.